Effect of Different Rearing Density on Survival Rate and Growth of Giant Gouramy Osphronemus gouramy Lac. Fry at Size of 2 cm in Length - I. Effendi; H.J. Bugri; . Widanarni (Jurnal Akuakultur Indonesia, 2007)
Giant gouramy Osphronemus gouramy Lac is one of the fish for food that has high economic value, but its production is not  met with the market demand yet.  The effort is needed to be done in order to increase production of giant gouramy fry by an intensive hatchery system through high rearing density.  This study was performed to determine the effect of rearing density on survival rate and growth of fry.  Fry were reared in aquaria 60x29x33 cm filled with 35 liters water, and fed by Tubifex at satiation as much as  0.23-0.28 g/fry/day with feeding frequency  2 times a day.   Collected  data were survival rate, growth, feed consumption, feed efficiency, and water quality.  The result of study showed that survival rate and feed efficiency did not affected by rearing density, while growth and feed quantity were did.  Survival rate of fish was high; 90.14-99.52%.  Growth and feed consumption were decreased by increasing of  rearing density.